2012
DOI: 10.1080/01431161.2012.666811
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different pan-sharpening methods for spectral characteristic preservation: multi-temporal CARTOSAT-1 and IRS-P6 LISS-IV imagery

Abstract: A host of remote-sensing and mapping applications require both high spatial and high spectral resolutions. Availability of high spatial and spectral details at different resolutions from a suite of satellite sensors has necessitated the development of effective image fusion techniques that can effectively combine the information available from different sensors and take advantage of their varied capabilities. A common problem observed in the case of multi-sensor multi-temporal data fusion is spectral distortio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Ghosh and Joshi (2013) utilized 12 fusion techniques to pansharpen WorldView-2 images, and the quantitative analysis indicated that high-pass filter, PANSHARP, GS and PCA method are the most efficient in increasing spatial resolution, while Brovey and Ehlers methods produced images with significant color distortion. Most research proved the advantages of GS method over IHS and Brovey method in terms of spectral quality preservation, spatial resolution enhancement and color distortion (Jalan and Sokhi, 2012;Yusuf et al, 2013).…”
Section: Comparison Of Different Image Pansharpening Methods On Soil mentioning
confidence: 99%
“…Ghosh and Joshi (2013) utilized 12 fusion techniques to pansharpen WorldView-2 images, and the quantitative analysis indicated that high-pass filter, PANSHARP, GS and PCA method are the most efficient in increasing spatial resolution, while Brovey and Ehlers methods produced images with significant color distortion. Most research proved the advantages of GS method over IHS and Brovey method in terms of spectral quality preservation, spatial resolution enhancement and color distortion (Jalan and Sokhi, 2012;Yusuf et al, 2013).…”
Section: Comparison Of Different Image Pansharpening Methods On Soil mentioning
confidence: 99%
“…Many research also compared different image pan-sharpened methods and their performance. Jalan and Sokhi (2012) showed high-pass filtering (HPF), Gram-Schmidt (GS) and PANSHARP methods produced comparable pan-sharpening images with high spectral quality and spatial enhancement, while Brovey method produced the pan-sharpening images with spatial enhancement but highly distorted radiometry. Karathanassi et al (2007) compared the 17 image pan-sharpening methods, local mean and variance matching (LMVM), least square fusion (LSF), and GS fusion methods have the highest performance in terms of peak signal-to-noise ratio (PSNR) and photointerpretation results.…”
Section: Introductionmentioning
confidence: 99%
“…Because each kind of imaging sensor can only focus on a given different operating spectral range and environmental conditions, it may not receive all the information necessary for detecting an object by human or computer vision. [16][17][18][19][20] Generally speaking, the methods producing high spatial quality may cause spectral distortion in the fused image. Fused images may provide improved interpretation capabilities and more reliable results since data with different characteristics are combined.…”
Section: Introductionmentioning
confidence: 99%